Light-induced Variation in Phenolic Compounds in Cabernet Sauvignon Grapes (Vitis vinifera L.) Involves Extensive Transcriptome Reprogramming of Biosynthetic Enzymes, Transcription Factors, and Phytohormonal Regulators - Sun, Run-Ze; Cheng, Guo; Li, Qiang; He, Yan-Nan; Wang, Yu; Lan, Yi-Bin; Li, Si-Yu; Zhu, Yan-Rong; Song, Wen-Feng; Zhang, Xue; Cui, Xiao-Di; Chen, Wu; et al. (Frontiers in Plant Science, 2017)
Light environments have long been known to influence grape (Vitis vinifera L.) berry development and biosynthesis of phenolic compounds, and ultimately affect wine quality. Here, the accumulation and compositional changes of hydroxycinnamic acids (HCAs) and flavonoids, as well as global gene expression were analyzed in Cabernet Sauvignon grape berries under sunlight exposure treatments at different phenological stages. Sunlight exposure did not consistently affect the accumulation of berry skin flavan-3-ol or anthocyanin among different seasons due to climatic variations, but increased HCA content significantly at véraison and harvest, and enhanced flavonol accumulation dramatically with its timing and severity degree trend. As in sunlight exposed berries, a highly significant correlation was observed between the expression of genes coding phenylalanine ammonia-lyase, 4-coumarate: CoA ligase, flavanone 3-hydroxylase and flavonol synthase family members and corresponding metabolite accumulation in the phenolic biosynthesis pathway, which may positively or negatively be regulated by MYB, bHLH, WRKY, AP2/EREBP, C2C2, NAC and C2H2 transcription factors. Furthermore, some candidate genes required for auxin, ethylene and abscisic acid signal transductions were also identified which are probably involved in berry development and flavonoid biosynthesis in response to enhanced sunlight irradiation. Taken together, this study provides a valuable overview of the light-induced phenolic metabolism and transcriptome changes, especially the dynamic responses of transcription factors and signaling components of phytohormones, and contributes to the further understanding of sunlight-responsive phenolic biosynthesis regulation in grape berries.